Workshop report: Climate-Smart Villages (CSVs). Ludhiana, India September 3-6th 2015 - CGIAR Research Program on Climate Change, Agriculture and Food Security (2015)
This 3-day workshop convened nearly 50 representatives from Climate-Smart Village related Flagship projects across Latin America, Africa, Asia and South Asia to share experiences and foster learning and exchange in order to: 1. Define a common vision of what CSVs are, their purpose to CCAFS and its partners, and direction moving forwards 2. Reflect on lessons learnt from different CCAFS regions and identify a set of best practices going forwards 3. Identify opportunities for harmonization of methodologies to enable cross regional analyses and global learning, and 4. Respond to emerging CCAFS external evaluation recommendations on CSVs and incorporate adjustments into Flagship projects during Extension and Phase 2 Plenary and fruitful group discussions, combined with field visits to the Haryana CSVs enabled deep reflections and the collective building of a common vision on the objectives, key elements and generic theory of change of CSVs. Various success stories of CSVs were highlighted including the development of climate-smart integrated portfolios based on holistic approaches, participatory action research and empowerment. CSVs were seen as particularly important models for articulation and partnerships between a variety of actors and institutions at all levels. Nevertheless, it was noted that certain areas had potential for improvement and this included concerns over the viability of sustainability beyond the project cycle, a lack of evidence of climate-smartness beyond productivity, a need to balance technology and socio-economic aspects, the need to better acknowledge indigenous knowledge, a lack of involvement of ‘poor’ farmers and youth, and more research, engagement and documentation needed to facilitate scaling out.